Pengaruh Motivasi Belanja Hedonis Terhadap Impulse Buying Konsumen Online Shop Di Instagram - Desi Defita Arifin (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
ABSTRACT               DESI DEFITA ARIFIN. 2016. "Effect of Motivation Shopping Hedonis Against Consumer Impulse Buying Online Shop On Instagram. Under the guidance of Mr. Pamasang S.Siburian as first counselor and mother Asnawati as second counselor.                The purpose of this study was to determine the effect of variable Adventure Shopping (X1), Relaxation Shopping (X2), Value Shopping (X3), Social Shopping (X4) and Idea Shopping (X5) to variable Impulse buying (Y) Consumer Online Shop on Instagram.               Based on the results obtained by analysis of multiple linear regression equation is Y = -22 093 + 0.1579X1 + 0.1466X2 0,1.729X3 + + + 0,1.659X5 0.254X4. F test results showed that the value of F (12 829 F table (2,669), which means variable Adventure Shopping (X1), Relaxation Shopping (X2), Value Shopping (X3), Social Shopping (X4) and Idea Shopping (X5) effect on variable Impulse buying (Y).               T test results showed that the value of the variable partial correlation Shopping Idea (X5) of 0548 with tcount (6641) t table (2,669) and significant 0.000. That is seen from the partial correlation value of 0548 or 54.8% that variable Idea Shopping (X5) is a dominant factor influencing Impulse buying variable (Y) on the online purchase shop in Instagram. Keyword : Adventure Shopping, Relaxation Shopping, Value Shopping, Social Shopping, Idea Shopping dan Impulse Buying.